Technology For Determining The Level Of Awareness And Understanding Of Primary School Children - Rakhimova Rano Bakhadirovna (Genius Publishing Group, 2024)
the effectiveness of working with the educational text in the article largely depends on the level of training of the reader. This connection concerns not only intellectual and cognitive manifestations of mental activity: it is reported that it covers all aspects of human personality activity
Keywords: comprehension; independent thinking; educational text